Histopathological evaluation of endometrial curettage in cases of abnormal uterine bleeding and its correlation with age of patient - Tilva, Khushbu K.; Jethwani, Deepa; Dhruva, Gauravi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Abnormal uterine bleeding (AUB) is defined as a pattern of bleeding that does not correspond with the duration, amount and frequency of the flow of a normal menstrual cycle. The cause of AUB varies according to the age, endometrial response to hormones and its variations and other structural lesions. Endometrial sampling by endometrium curettage is safe and easy technique and its histopathological analysis is considered the gold standard for diagnosis of the etiology of AUB. Aims and objective was to evaluate the spectrum of endometrial histology in cases of AUB, to find out age wise incidence of AUB, and to find out age wise incidence of various histological pattern of endometrium in AUB. Methods: An observational study was conducted on dilatation and curettage material which were obtained from 110 women with a complaint of AUB attending the gynecology outpatient department (OPD) at tertiary care hospital, Rajkot, Gujarat during one year (August 2020 to July 2021). Results: Maximum number of cases of AUB were noted in the age group of (31-40) years (44 cases, 40%). Most common observed histopathological pattern in this study was normal cyclical patterns including proliferative endometrium (34.5%) and secretory endometrium (21%). Conclusions: Histopathological evaluation of endometrium is indicated in women over the age of 35 years presenting with AUB to rule out preneoplastic lesions and malignancies.